Application of Quantum Computing in Optimization Problems (MCIT: Proceedings of International scientific and practical conference, 2025)
The article examines methods for applying quantum computing to solve optimization problems, which are critical in various fields such as logistics, finance, resource management, energy, and others. The potential of quantum algorithms, such as Grover's algorithm and Variational Quantum Algorithms (VQA), is explored for enhancing computational efficiency compared to classical methods. Quantum computing enables significant acceleration of optimal solution search processes and reduces the complexity of problems through parallel computing and quantum superposition.
Keywords: quantum computing; optimization; quantum algorithm; quantum variational algorithm; Grover's search